Hemopoietic Activity of the Beetroot Ethanolic Extract of Beta Vulgaris (Shamandar) in Albino Rats - Shahbaa M. Al-Khazraji (Journal of Global Pharma Technology, 2018)
Beta vulgaris known locally as shamandar, the aim of this study is to demonstrate the hem biotic effect of the ethanolic extract of beetroot of the plant, The study was prepared to investigate the effect on hemoglobin (Hb), red blood cell count (RBC) “, packed cell volume (PCV) “, mean corpuscular hemoglobin (MCH) “, mean corpuscular volume (MCV)”, and mean corpuscular hemoglobin concentration (MCHC) “by using 50 albino Swiss rats. Five groups of rats (each 10) were fed orally with different doses of beetroot extract of Beta vulgaris (200, 400, 800, 1600 mg/kg body weight and control), for sixteen days. Blood samples were collected from the rats by ocular bleeding, and analyzed for the determination of the hem biotic parameters. It is concluded from the study , that the beetroot ethanolic extract of beta vulgaris elevate the blood parameters in a dose dependant  manner , which support the folklore  use of the juice of the shamandar to treat anemia.Keywords:  Beta vulgaris, Shamandar,   Beetroot, Albino Rats, Blood Picture, anemia.